Penerapan Sistem Pendukung Keputusan Penerima Bantuan Langsung Tunai Menggunakan Metode Smart : Studi Kasus: Desa Padaeweta Kecamatan Wewewa Timur - Apliana Kartini Sangga; Adelbertus Umbu Janga; Sihang Gregorius Bali Mema (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Family Welfare Empowerment (PKK) is a community organization that plays a vital role in improving family welfare in Indonesia. Through various programs, the PKK contributes to family empowerment, particularly in education, health, and economics. However, many PKK activities are still conducted manually, including recording and managing member data and activities. This creates several challenges, such as difficulty in archiving, time-consuming information searches, and difficulties in preparing accurate and timely reports. This research aims to design and develop a web-based information system that can simplify member data management, activity recording, attendance management, and report generation more quickly, efficiently, and accurately. This system will be designed using an object-oriented approach, involving several stages, starting from needs analysis, system design, implementation, and system testing. This information system is expected to improve service efficiency, facilitate PKK administrators in monitoring member activity, and support a more precise and weighted data-based decision-making process. Another advantage is that this system will also facilitate the PKK in producing faster, more comprehensive, and more structured activity reports, thereby increasing organizational transparency and accountability. Therefore, this web-based information system is expected to be a solution to improve the PKK's performance in carrying out its function of empowering family welfare.